Effects of an active break and postural shift intervention on preventing neck and low-back pain among high-risk office workers: a 3-arm cluster-randomized controlled trial - Pooriput Waongenngarm; Allard J van der Beek; Nipaporn Akkarakittichoke; Prawit Janwantanakul (Nordic Association of Occupational Safety and Health (NOROSH), 2021)
OBJECTIVE: This study evaluated the effects of the promotion of active breaks and postural shifts on new onset of neck and low-back pain during a 6-month follow-up among high-risk office workers. METHODS: A 3-arm cluster-randomized controlled trial with 6-month follow-up was conducted among healthy but high-risk office workers. Participants were recruited from six organizations in Bangkok, Thailand (N=193) and randomly assigned at cluster level into active break intervention (N=47), postural shift intervention (N=46), and control (N=100) groups. Participants in the intervention groups received a custom-designed apparatus to facilitate designated active breaks and postural shifts during work. Participants in the control group received a placebo seat pad. The primary outcome measure was new onset of neck and low-back pain during 6-month follow-up. Analyses were performed using Cox proportional hazard models. RESULTS: One-hundred and eighty-six (96%) predominantly female participants were successfully followed up over six months. New onset of neck pain during the 6-month follow-up occurred in 17%, 17%, and 44% of the participants in the active break, postural shift, and control groups, respectively. For new onset of low-back pain, these percentages were 9%, 7%, and 33%, respectively. Hazard rate (HR) ratios after adjusting for biopsychosocial factors indicated a protective effect of the active break and postural shift interventions for neck pain [HRadj 0.45, 95% confidence interval (CI) 0.20-0.98 for active break and HRadj 0.41, 95% CI 0.18-0.94 for postural shift] and low-back pain (HRadj 0.34, 95% CI 0.12-0.98 for active break and HRadj 0.19, 95% CI 0.06-0.66 for postural shift). CONCLUSION: Interventions to increase either active breaks or postural shifts reduced new onset of neck and low-back pain among high-risk office workers.